Chemical weathering outputs from the flood plain of the Ganga. (15th March 2018) - Bickle, Michael J.; Chapman, Hazel J.; Tipper, Edward; Galy, Albert; De La Rocha, Christina L.; Ahmad, Talat
Abstract: Transport of sediment across riverine flood plains contributes a significant but poorly constrained fraction of the total chemical weathering fluxes from rapidly eroding mountain belts which has important implications for chemical fluxes to the oceans and the impact of orogens on long term climate. We report water and bedload chemical analyses from the Ganges flood-plain, a major transit reservoir of sediment from the Himalayan orogen. Our data comprise six major southern tributaries to the Ganga, 31 additional analyses of major rivers from the Himalayan front in Nepal, 79 samples of the Ganga collected close to the mouth below the Farakka barrage every two weeks over three years and 67 water and 8 bedload samples from tributaries confined to the Ganga flood plain. The flood plain tributaries are characterised by a shallow δ 18 O - δD array, compared to the meteoric water line, with a low δDexcess from evaporative loss from the flood plain which is mirrored in the higher δDexcess of the mountain rivers in Nepal. The stable-isotope data confirms that the waters in the flood plain tributaries are dominantly derived from flood plain rainfall and not by redistribution of waters from the mountains. The flood plain tributaries are chemically distinct from the major Himalayan rivers. They can be divided into two groups. Tributaries from a small area around the Kosi river have 87 Sr/ 86 Sr ratios >0.75 and molar Na/Ca ratios as high as 6. Tributaries from the rest of the flood plain have 87 Sr/ 86 Sr ratios ≤0.74 and most have Na/Ca ratios <1. One sample of the Gomti river and seven small adjacent tributaries have elevated Na concentrations likely caused by dissolution of Na carbonate salts. The compositions of the carbonate and silicate components of the sediments were determined from sequential leaches of floodplain bedloads and these were used to partition the dissolved cation load between silicate and carbonate sources. The 87 Sr/ 86 Sr and Sr/Ca ratios of the carbonate inputs were derived from the acetic-acid leach compositions and silicate Na/Ca and 87 Sr/ 86 Sr ratios derived from silicate residues from leaching. Modelling based on the 87 Sr/ 86 Sr and Sr/Ca ratios of the carbonate inputs and 87 Sr/ 86 Sr ratios of the silicates indicates that the flood plain waters have lost up to 70% of their Ca (average ∼ 50%) to precipitation of secondary calcite which is abundant as a diagenetic cement in the flood plain sediments. 31% of the Sr, 8% of the Ca and 45% of the Mg are calculated to be derived from silicate minerals. Because of significant evaporative loss of water across the flood plain, and in the absence of hydrological data for flood plain tributaries, chemical weathering fluxes from the flood plain are best calculated by mass balance of the Na, K, Ca, Mg, Sr, SO4 and 87 Sr/ 86 Sr compositions of the inputs, comprising the flood plain tributaries, Himalayan rivers and southern rivers, with the chemical discharge in the Ganga at Farakka. The calculated fluxes from the flood plain for Na, K, Ca and Mg are within error of those estimated from changes in sediment chemistry across the flood plain (Lupker et al., 2012, Geochemica Cosmochimica Acta). Flood plain weathering supplies between 41 and 63% of the major cation and Sr fluxes and 58% of the alkalinity flux carried by the Ganga at Farakka which compares with 24% supplied by Himalayan rivers and 18% by the southern tributaries.